Living with dinosaurs - Lauber, Patricia; Henderson, Doug (New York : Maxwell Macmillan International Pub. Group, 1991)
Recreates life among the dinosaurs living in North America seventy-five million years ago.
Includes index.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
5.1
5.1
Keywords: Dinosaurs -- North America -- Juvenile literature; Dinosaurs; Dinosaurs